2018
DOI: 10.31665/jfb.2018.3158
|View full text |Cite
|
Sign up to set email alerts
|

Anti-diabetic effects of a theaflavin-enriched black tea extract in the obese ZDF rat model

Abstract: Effects of a theaflavin-enriched black tea extract (BTE) against type 2 diabetes (T2D) were analyzed using the obese ZDF model. ZDF rats were hyperglycemic, dyslipidemic and express pro-inflammatory markers. BTE was well tolerated and caused an elevation of fasted and fed glucose as well as lower glucose tolerance in contrast to hypoglycemic effects by metformin. However, the BTE group showed decreased levels of LDL and triacylglycerols which corresponded to an increase in free fatty acids. Positive effects ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Therefore, catechins from green tea are responsible for the reduction of insulin resistance, while theaflavins in black tea play a critical role in stimulating β-cell insulin secretion (Tang et al, 2013), indicating different hypoglyceamic mechanisms by catechins and theaflavins. Further anti-diabetic effects of TF-BTE was confirmed in an obese ZDF rat model with findings of anti-inflammatory activity of theaflavins (Gosslau et al, 2018).…”
Section: Different Hypoglycemia Mechanism With Different Profil?s Of mentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, catechins from green tea are responsible for the reduction of insulin resistance, while theaflavins in black tea play a critical role in stimulating β-cell insulin secretion (Tang et al, 2013), indicating different hypoglyceamic mechanisms by catechins and theaflavins. Further anti-diabetic effects of TF-BTE was confirmed in an obese ZDF rat model with findings of anti-inflammatory activity of theaflavins (Gosslau et al, 2018).…”
Section: Different Hypoglycemia Mechanism With Different Profil?s Of mentioning
confidence: 61%
“…Obesity and T2D are closely correlated with each other and also with chronic inflammation. Tea polyphenols exert hypoglycemic activity (Tang et al, 2013;Miao et al, 2015;Huang et al, 2015;Gosslau et al, 2018). Tea extracts in the market vary dramatically in their content and type of bioactive chemical entities, particularly polyphenols, which can be very much misleading when referring to anti-diabetic activity of tea extracts in the absence of characterization of compounds involved.…”
Section: Different Hypoglycemia Mechanism With Different Profil?s Of mentioning
confidence: 99%
“…Accordingly, several sources of phenolic compounds have been tested for their inhibitory activity toward alpha-glucosidase [ 66 , 67 ]. The antidiabetic effect of natural compounds has been in the spotlight of various researchers [ 68 , 69 ]. Alpha-glucosidase, an enzyme found in the brush border of the small intestine, inhibits the absorption of carbohydrates and may suppress the postprandial blood glucose and insulin levels, while pancreatic lipase is a key enzyme regulating the absorption of triacylglycerols [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 17,43 ] Catechin polymers, formed under the high temperature conditions, may also contribute to the activities of YTE; several reports showed that catechin dimers theaflavins lowered body lipid in obese rat, [ 44 ] and theaflavin‐enriched black tea extract protected against obesity‐related inflammation in the obese ZDF rat model. [ 45 ] Careful studies on the active compounds in YTE for the induction of thermogenesis are essential for elucidating the detailed mechanisms involved.…”
Section: Discussionmentioning
confidence: 99%